«Ընկալում, կարծիք, վերաբերմունք» արտահայտող դարձվածքները հայերենում, ռուսերենում և անգլերենում - Ղազարյան, Հ. Զ.
С помощью метонимии, являющейся одним из наиболее действенных стилистических приемов, придающих речи образность, образуется множество фразеологизмов. Среди них важное место занимают фразеологизмы, включающие названия частей тела. Целью данной статьи является исследование, анализ и сопоставление особенностей армянских, русских и английских фразеологизмов с компонентов ‟глаз”, выражающих восприятие, отношение и мнение. Выявлены некоторые общие и различительные черты семантические, структурные, грамматические и стилистические особенности фразеологизмов рассмотренных языков, что указывает на общность и различие в языковом мышлении народов, говорящих на данных языках. Numerous phraseological units are formed by the stylistic device metonymy which is one of the most active devices, making the speech figurative and expressive. Among these phraseological units, there are a great number of phraseological units, including names of body parts. The goal of the article is to investigate, analyze and compare the peculiarities of the Armenian, Russian and English phraseological units with the component ‟eyeˮ, expressing perception, attitude and opinion. Some similarities and differences of the mentioned peculiarities are revealed in the semantic, structural, grammatical and stylistic characteristics of the units of the languages considered, which speaks about the similarities and differences between the linguistic thinking of the people speaking the given language.
Keywords: Լեզվաբանություն